Analysis of the promoter and cis-acting elements regulating expression of herpes simplex virus type 2 latency-associated transcripts. - Wang, K (1995)
In latently infected neurons, herpes simplex virus type 2 (HSV-2) expresses one abundant family of transcripts, the latency-associated transcripts (LATs). We demonstrate here that the sequence lying about 700 bp upstream of the 5' end of the HSV-2 major LAT acts as a very strong promoter in transient expression assays in both neuronal and nonneuronal cells. Transcription starts about 27 to 32 bp downstream of a functional TATA box. The proximal fragment from -102 to +34 includes the basal promoter and accounts for constitutive transcriptional activity in various cell lines. The distal region from -392 to -103 contributes to particularly strong promoter activity in neuronal cell lines and involves multiple cis-acting elements. A functional activating transcription factor/cyclic AMP (cAMP) response element binding protein motif lies just upstream of the TATA. By DNase I footprint and methylation protection assays, we identified several additional protein-binding sites upstream of the activating transcription factor/cAMP response element binding protein motif. A GC-rich element, termed LAT-3, was located between bases -128 to -102. A 2-bp substitution in LAT-3 markedly reduced promoter activity and abolished protein-binding ability in vitro. Gel retardation assay showed no competition for protein binding to LAT-3 by other GC-rich elements. LAT-3 appears to be a novel cis-acting element that may contribute to the neuronal responsiveness of the HSV-2 LAT promoter.